An Investigation of Electronic Structure and Aromaticity in Medium-Sized Nanoclusters of Gold-Doped Germanium. (6th December 2012) - Li, Xiao-Jun; Ren, Hong-Jiang; Yang, Li-Ming
Abstract : The electronic property and aromaticity of endohedrally doped A u G e 10 - and A u G e 12 - clusters are investigated using the density-functional theory (DFT) within the hybrid B3LYP method. The calculated results reveal that the two clusters have high thermodynamic stability reflected by reaction energy. At the same time, it could be hoped that their high stability may arise from the closed-shell spherical aromaticity with eight π -electrons satisfying the 2 ( N n + 1 ) 2 counting rule with N π = 1 . A popular nucleus-independent chemical shifts (NICSs) calculation on basis of magnetic shieldings is also performed to confirm the aromaticity of the three-dimensional nanoclusters with largely negative NICS values. In addition, the electronic features and chemical bonding of the two clusters are analyzed with the help of the density of states (DOS) and electron localization function (ELF), and the majority of Ge–Ge bonds on the cage show more covalent characters.